2022
DOI: 10.1002/jcla.24336
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammation‐immunity‐nutrition score in patients with hepatocellular carcinoma treated with anti‐PD‐1 therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Recent studies have shown that inflammatory biomarkers are closely associated with postoperative prognosis in patients with cancer, including HCC. 14,[18][19][20] However, the value of IINS and IBI in predicting prognosis in HCC patients after hepatectomy has not been explored. Here, we investigated IINS and IBI as potential predictors of poor DFS and OS and compared the performance of models based on IINS, IBI or both, in combination with other inflammation and nutrition markers and clinical staging systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that inflammatory biomarkers are closely associated with postoperative prognosis in patients with cancer, including HCC. 14,[18][19][20] However, the value of IINS and IBI in predicting prognosis in HCC patients after hepatectomy has not been explored. Here, we investigated IINS and IBI as potential predictors of poor DFS and OS and compared the performance of models based on IINS, IBI or both, in combination with other inflammation and nutrition markers and clinical staging systems.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The inflammation-immunity-nutrition score (IINS), a combination of C-reactive protein (CRP), lymphocyte (LYM) count and serum albumin (ALB) level, 12 has shown promising prognostic performance in colorectal cancer, 12 endometrial cancer, 13 and HCC treated with therapy targeting programmed cell death protein 1. 14 Similarly, the inflammatory burden index (IBI) is also a potential inflammatory biomarker that can be used to predict prognosis in patients with colorectal cancer, esophageal cancer, gastric cancer, 15 pancreatic cancer 16 or bladder cancer. 17 To our knowledge, neither the IINS nor IBI has been assessed for its ability to predict prognosis of HCC patients after hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study defined the inflammation‐immunity‐nutrition score (IINS), which was simply based on highly sensitive C-reactive protein (hsCRP), LYM, and ALB ( 50 ). HCC Patients with low IINS had longer OS and PFS in response to anti-PD-1, suggesting that IINS may serve as an independent prognostic factor for HCC patients treated with anti‐PD‐1 therapy ( 51 ).…”
Section: Blood-based Biomarkers For Immune-based Treatment In Advance...mentioning
confidence: 99%
“…The 3.5 gr/dL was the most frequently used albumin cut-off in the included studies (n = 20) [25, 31-33, 37, 38, 40-43, 45-52, 54, 56-64], while eight studies evaluated the effect of albumin levels on survival by using albumin as a continuous measure [34,39,44,53,55,[65][66][67]. All but two studies reported HR for OS [25,36,49], while data for PFS was available in the 15 studies [25, 32, 33, 36, 40-42, 48-50, 52, 53, 57, 60, 63, 66]. Most studies tested the prognosis in patients treated with ICI monotherapy and nivolumab was the most commonly used ICI in the studies (n = 21) (Table -…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fifteen studies were included in the meta-analyses for PFS [25, 32, 33, 36, 40-42, 48-50, 52, 53, 57, 60, 63, 66]. Nine studies were reported signi cantly lower PFS in patients with lower albumin levels, while the association between the albumin levels and PFS was not reached statistical signi cance in remaining six studies [32,49,50,53,57,66]. In the meta-analysis of fteen studies, the patients with lower albumin levels had increased risk of progression or death compared to patients with higher albumin levels (HR: 1.74, 95% CI: 1.39-2.17, p<0.001) (Figure 4).…”
Section: The Association Between Hypoalbuminemia and Progression-free...mentioning
confidence: 99%